2013
DOI: 10.1111/and.12103
|View full text |Cite
|
Sign up to set email alerts
|

Determination of retinol and α-tocopherol in human seminal plasma using an HPLC with UV detection

Abstract: Oxidative stress has been proposed as one of the potential causes for infertility in men. Retinol and α-tocopherol have an important role in the spermatozoa defences against oxidative stress. A method is described here for the simultaneous determination of retinol and α-tocopherol in human seminal plasma with a suitable sample preparation procedure to prevent retinol and α-tocopherol degradation. After adequate sample preparation, the samples were determined by reversed-phase column chromatography with UV dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
4
10
0
Order By: Relevance
“…The validated method was successfully applied for the determination of concentrations of retinol, α ‐tocopherol, 25‐OH‐D2 and 25‐OH‐D3 in plasma samples of patients with cardiovascular disease. These concentrations are similar to those reported by other authors for patients with cardiovascular disease (Kanďár, Drábková, Myslíková, & Hampl, ; Robinson‐Cohen et al, ; Wang et al, ) and healthy volunteers (Jenab et al, ; Midttun & Ueland, ; Table ). Several studies showed an association between plasma levels of fat‐soluble antioxidant vitamins and atherosclerotic progression in arteries (Kanďár et al, ; Polidori et al, ; Riccioni et al, ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The validated method was successfully applied for the determination of concentrations of retinol, α ‐tocopherol, 25‐OH‐D2 and 25‐OH‐D3 in plasma samples of patients with cardiovascular disease. These concentrations are similar to those reported by other authors for patients with cardiovascular disease (Kanďár, Drábková, Myslíková, & Hampl, ; Robinson‐Cohen et al, ; Wang et al, ) and healthy volunteers (Jenab et al, ; Midttun & Ueland, ; Table ). Several studies showed an association between plasma levels of fat‐soluble antioxidant vitamins and atherosclerotic progression in arteries (Kanďár et al, ; Polidori et al, ; Riccioni et al, ).…”
Section: Resultssupporting
confidence: 90%
“…These concentrations are similar to those reported by other authors for patients with cardiovascular disease (Kanďár, Drábková, Myslíková, & Hampl, ; Robinson‐Cohen et al, ; Wang et al, ) and healthy volunteers (Jenab et al, ; Midttun & Ueland, ; Table ). Several studies showed an association between plasma levels of fat‐soluble antioxidant vitamins and atherosclerotic progression in arteries (Kanďár et al, ; Polidori et al, ; Riccioni et al, ). A significant correlation was also confirmed between vitamin D deficiency and incident cardiovascular disease (Judd & Tangpricha, ; Wang et al, ).…”
Section: Resultssupporting
confidence: 90%
“…methanol) to optimize selectivity . Several methods for the determination of lipovitamins in biological fluids involve chromatographic separation using UV–Vis or fluorescence detection (FLD) . The LODs and LOQs of these methods are usually sufficient for the analysis of carotenoids, retinoids, and tocopherols with appropriate precision and accuracy.…”
Section: Fat‐soluble Vitaminsmentioning
confidence: 99%
“…However, HPLC–FLD methods showed multiple improvements to the sensitivity in comparison with the HPLC–UV methods. For example, LOQ of α‐tocopherol obtained by UV was 0.2 μM , while the value of 21.4 nM was reached by FLD . Measurement of other analytes, such as vitamin K derivatives or vitamin D hydroxy metabolites, is limited because of their low concentrations in the blood.…”
Section: Fat‐soluble Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation